Integrasi Nilai-nilai Keislaman dan Kemuhammadiyahan dalam Pembelajaran Zakat dan Waris pada Kurikulum Matematika Sekolah Muhammadiyah - Ferra Fijantari; Mhd. Lailan Arqam (EduInovasi: Journal of Basic Educational Studies, 2025)
Muhammadiyah education integrates Islamic and Muhammadiyah values ​​in learning, including mathematics, to form students who excel intellectually and spiritually through materials such as zakat and inheritance. However, the implementation of this integrative curriculum still faces challenges, such as limited teacher understanding, minimal references, and lack of systematic guidance, so that effective and applicable learning strategies and modules are needed. This study uses a qualitative approach with a historical method to analyze the integration of Islamic and Muhammadiyah values ​​in the mathematics curriculum, especially the material on zakat and inheritance in Muhammadiyah schools, with secondary data analyzed qualitatively through data reduction, presentation, and triangulation of sources to ensure data validity. This study concludes that the integration of Islamic and Muhammadiyah values ​​in zakat and inheritance learning in the mathematics curriculum of Muhammadiyah Schools is effective in shaping students' character and improving their understanding of mathematical concepts. This approach successfully links mathematical concepts with the values ​​of justice, honesty, and social concern, as well as strengthening students' motivation and religious awareness. Despite challenges related to limited resources and teacher training, positive impacts on students' cognitive, affective, and spiritual aspects are still evident. To improve its effectiveness, it is recommended to develop comprehensive teaching materials, more intensive teacher training, and stronger collaboration between teachers. Keywords: Integration of Islamic Values, Muhammadiyah, Mathematics Curriculum, Zakat and Inheritance Learning, Muhammadiyah Education